Design of Augmented Reality as Digital Teaching Media English Vocabulary: Word Warrior - Lukcyhasnita, Andam; Tumanggor, Orli Binta; Syafitri, Winda; Siregar, Dina Arfianti; Juneidy (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The need for digital learning innovation is one of the latest issues. Especially in learning English. This is because Indonesia, based on the English Proficiency Index, or EPI (English Proficiency Index), is ranked 81st out of 111 countries in the world and is ranked 15th out of 24 countries in Asia with low English proficiency status results. So, in order to encourage English language skills, innovative efforts are needed in English language learning that can generate interest in learning. Especially in delivering English vocabulary teaching materials. Therefore, this research aims to produce a multimedia product that can be applied as an interactive teaching medium for English vocabulary. To achieve the output, this research used the Research and Development research method, using research steps consisting of (1) Define, (2) Design, (3) Development, and (4) Dissemination. However, this research is limited to the development level, so the final result of this research is a digital medium in the form of an Instagram vocabulary game filter game called Word Warrior. This filter game carries vocabulary games with correct spelling.